Rancang Bangun Sistem Rekomendasi Restoran Menggunakan Metode AHP dan VIKOR pada Platform LINE - Andre Utomo Martliong; Ni Made Satvika Iswari (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2018)
Since 2012 until 2017, culinary business in Indonesia has increased by an average 7% to 14% per year. Nowadays, application technology such as Zomato, helps consumers to find information about restaurant’s promos, advantages and disadvantages of a restaurant, and variations of the menu their provided. People who owned the culinary business can interact directly with consumers through social media such as LINE. LINE has 90 million users that communicate with each other by using features that LINE’s provided, such as stickers, news portals, voice and video calls, and LINE Message API service. With 90 million LINE’s users in Indonesia and growing culinary business, developing a restaurant recommendation system in LINE will provide solutions to many people, which inspired the author to develop this system. Data of restaurant it’s taken using Zomato API. Developing this system needs a method of AHP (Analytic Hierarchy Process) and VIKOR (VIsektriterijumsko KOmpromisno Rangiranje), where the application will be built using PHP language. The AHP method is used to assign a weighting value to criteria, and the VIKOR method is used to sort the best alternative option. Based on research through questionnaires, this system’s design and implementation has reached 71,13 value of usability, which mean that system is useful to help people to find restaurant their looking for. Index Terms - Culinary, Zomato API, LINE Message API, AHP, VIKOR